Strategi Badan Pengawas Pemillihan Umum (Bawaslu) dalam Mengawasi Pelaksanaan Pemilu Tahun 2024 di Kabupaten Pesisir Selatan - Amanda, Natasha; Adnan, M. Fachri (Lembaga Yasin AlSys, 2025)
This research discusses Bawaslu strategy in supervising the implementation of the 2024 General Election in Pesisir Selatan Regency. The issues raised are the strengths, weaknesses, opportunities and threats of Bawaslu in ensuring elections run honestly, considering the many potential events that occur during the election process. This research aims to identify and analyze Bawaslu strategy in dealing with weaknesses and threats as well as monitoring efforts carried out in order to improve the quality of elections. The method used in this research is a qualitative approach with descriptive research type. Data was collected through in-depth interviews with members of Bawaslu, KPU, Prosecutor's Office, PTPS, members of political parties and the public, as well as studying documentation related to the election. To test the validity of the data, source and technical triangulation techniques were used. Data analysis was carried out using qualitative analysis techniques, namely data reduction, data presentation, and drawing conclusions. The research results show that Bawaslu strategy in Pesisir Selatan Regency includes increasing awareness and strengthening compliance with election regulations, coordinating with relevant stakeholders, increasing community participation in supervision, and applying technology in supervision. Even though there are several weaknesses and threats such as limited human resources, limited time, limited authority in taking action and geographical conditions, Bawaslu continues to try to optimize its supervisory role to ensure fair and accountable elections.